Complex and Diverse Morphologies Can Develop from a Minimal Genomic Model - Fernández-Rodríguez, Jose David; Vico-Vela, Francisco José; Doursat, René (My University, 2013)
While development plays a critical role in the emergence of diversity, its mechanical and chemical actions are considered to be inextricably correlated with genetic control. Since in most extant species the complex growth from zygote to adult organism is orchestrated by a complex gene regulatory network (GRN), the prevalent view is that the evolution of diverse morphologies must result from the evolution of diverse GRN topologies. By contrast, this work focuses on the unique e ect of developmental processes through an abstract model of self-regulated structure without genetic regulation|only modulation of initial conditions. Here, morphologies are generated by a simple evolutionary algorithm searching for the longest instances of unfolding dynamics based on tensegrity graphs. The usual regulatory function of the genome is taken over by physical constraints in the graphs, making morphological diversity a pure product of structural complexi cation. By highlighting the potential of structural development, our model is relevant to both "structuralist" biological models and bio-inspired systems engineering.
Keywords: Biología computacional; Computational biology; Evolutionary development; Morphogenesis; Indirect encoding; Tensegrity